10 K high frequency pulse tube cryocooler with precooling. (July 2016) - Liu, Sixue; Chen, Liubiao; Wu, Xianlin; Zhou, Yuan; Wang, Junjie
Highlights: A high frequency pulse tube cryocooler with precooling was designed, manufactured, and tested. The stainless steel meshes are used as regenerative material completely for the pulse tube cryocooler. A minimum no-load refrigeration temperature 10.3 K was obtained, and the cooling power was 264 mW@15 K and 922 mW@20 K. Abstract: A high frequency pulse tube cryocooler with precooling (HPTCP) has been developed and tested to meet the requirement of weak magnetic signals measurement, and the performance characteristics are presented in this article. The HPTCP is a two-stage pulse tube cryocooler with the precooling-stage replaced by liquid nitrogen. Two regenerators completely filled with stainless steel (SS) meshes are used in the cooler. Together with cold inertance tubes and cold gas reservoir, a cold double-inlet configuration is used to control the phase relationship of the HPTCP. The experimental result shows that the cold double-inlet configuration has improved the performance of the cooler obviously. The effects of operation parameters on the performance of the cooler are also studied. With a precooling temperature of 78.5 K, the maximum refrigeration capacity is 0.26 W at 15 K and 0.92 W at 20 K when the input electric power are 174 W and 248 W respectively, and the minimum no-load temperature obtained is 10.3 K, which is a new record on refrigeration temperature for high frequency pulse tube cryocooler reported with SS completely used as regenerative matrix.